Current Cardiology Reports - Nissen, Steven E.; Erbel, Raimund; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The aim of this journal is to provide timely perspectives from experts on current advances in cardiovascular medicine. We also seek to provide reviews that highlight the most important recently published papers selected from the wealth of available cardiovascular literature. We accomplish this aim by appointing key authorities in major subject areas across the discipline. Section editors select topics to be reviewed by leading experts who emphasize recent developments and highlight important papers published over the past year. An Editorial Board of internationally diverse members suggests topics of special interest to their country/region and ensures that topics are current and include emerging research. We also provide commentaries from well-known figures in the field.
Keywords: Cardiology; Cardiology